The Concept of Evaluating the Fiqh Learning Process Using the CIPP Model - Andhika Sarfatra Winarno; Joko Subando (Didaktika: Jurnal Kependidikan, 2025)
The quality of education is influenced by many factors, including students, school administrators, the environment and quality of teaching, curriculum and so on. Efforts to improve education can be taken by improving the quality of learning and a good evaluation system. Both are interrelated in the learning system. This study aims to evaluate the Fiqh Akhlak learning process at SDIT Al Madinah Putra Nogosari Boyolali. The method used is qualitative research with the CIPP model which emphasizes the process. The results of the study, namely in learning preparation, found that teachers had prepared RPP consisting of 4 components, namely: Learning Objectives (SPP), Implementation, Learning Achievements (CP), and Assessment. This shows that the RPP prepared by teachers has been in accordance with the minimum component standards because the standards set by the government in Permendikbud Number 16 of 2022 include 3 components. Teachers have also implemented learning in accordance with the standards set in Permendikbud Number 22 of 2022. Namely, fulfilling 7 points out of 10 criteria points in the Permendikbud: 1) Contextual Learning Approach, 2) Utilization of Technology, 3) Utilization of Learning Resources, 4) Diversification of Learning, 5) Collaboration and Interaction. This research is expected to provide a significant contribution to the development of the quality of Islamic education, especially in learning Fiqh Akhlak. An in-depth evaluation of the learning process will produce a comprehensive understanding of the effectiveness of teaching methods, the suitability of the curriculum, and the achievement of student competencies in forming noble morals and characters.